Meta-Analysis: Effects of Knowledge and Training on the Readiness of Electronic Medical Record Use in Health Workers - Prasetya, Hanung; Ma'ruf, Agus Syukron; Murti, Bhisma (Journal of Health Policy and Management, 2024)
Background: Globally, more than half of RME projects face the potential problem that only 35% of lower-middle-income countries and 15% of low-income countries have implemented national electronic health record systems. This study aims to analyze previous primary studies in assessing the influence of electronic medical record training and level of knowledge on health workers' readiness to use electronic medical records. Subjects and Method: This research is a systematic review and meta-analysis using the PRISMA flow diagram and PICO model. Population: health workers. Intervention: RME training and level of knowledge. Comparison: no RME training and poor knowledge level. Outcome: readiness to use RME in health workers. The databases used were Google Scholar, Pubmed, ScienceDirect, Taylor & Francis, Springer Link, Plos One, and BioMed Central, with the keywords (“Willingness” OR “Readiness” OR “Utilization” AND “Electronic Medical Records” OR “EMR” AND “Training” OR “EMR Training” AND “Knowledge” AND 46 “Health Professionals” AND “Cross Sectional” AND “Adjusted Odds Ratio” OR “AOR”). There were 9 cross-sectional studies published in 2015-2023 that met the inclusion criteria. Data analysis using RevMan 5.4. Results: Meta-analysis of 9 articles with a cross-sectional study design obtained from Ethiopia with a sample size of 3,996 health workers. The meta-analysis results show that health workers who received EMR training were 2.62 times more prepared to use electronic medical records compared to health workers who did not receive EMR training, and these results were statistically significant (aOR= 2.62; 95% CI= 2.01 to 3.42; p = 0.001), Health workers who have good knowledge can increase readiness to use electronic medical records by 1.83 times compared to health workers who have poor knowledge, and these results are statistically significant (aOR= 1.83; 95% CI= 1.50 to 2.24; p= 0.001). Conclusion: Health workers who receive RME training and have a good level of knowledge can increase their readiness to use RME. Keywords: RME training, level of knowledge, RME readiness, health personnel Correspondence: Agus Syukron Ma’ruf. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: syukron.agsyma2901@itsk-soepraoen.ac.id. Mobile: +6281333387010.